In vivo deciduous dental eruption in LuiKotale bonobos and Gombe chimpanzees. Issue 4 (26th July 2021) - Lee, Sean M.; Sutherland, L. J.; Fruth, Barbara; Murray, Carson M.; Lonsdorf, Elizabeth V.; Arbenz‐Smith, Keely; Augusto, Rafael; Brogan, Sean; Canington, Stephanie L.; Lee, Kevin C.; McGrath, Kate; McFarlin, Shannon C.; et al.
Abstract: Objectives: Existing data on bonobo and chimpanzee dental eruption timing are derived predominantly from captive individuals or deceased wild individuals. However, recent advances in noninvasive photographic monitoring of living, wild apes have enabled researchers to characterize dental eruption in relatively healthy individuals under naturalistic conditions. At present, such data are available for only one population of wild chimpanzees. We report data for an additional population of wild chimpanzees and the first dental eruption data for wild bonobos. Materials and Methods: We collected photographs and video footage of teeth from the open mouths of wild bonobos and East African chimpanzees of known age from LuiKotale, Democratic Republic of the Congo, and Gombe National Park, Tanzania, respectively. We scored the presence and absence of deciduous teeth from photographs and video footage to characterize deciduous dental eruption timing in these two populations. Results: Deciduous dental eruption ages in our sample fall within the range of variation previously documented for captive chimpanzees, but eruption ages are later in wild than in captive contexts. We found substantial variation in deciduous canine eruption timing, particularly among bonobos. One bonobo had a deciduous canine present by 227 days old while another did not have a deciduous canine present at 477 days old. Discussion: Our data indicate that deciduous teeth erupt later in wild individuals than in captive individuals. We also found that deciduous dental eruption timing varies considerably between individuals within our study populations, a pattern that is consistent with previous studies. Future studies should consider sources of variation in deciduous canine eruption timing and relationships with other aspects of life history as additional data become available. Abstract : Representative sample of wild bonobo and chimpanzee deciduous dentition photographic data used in this study.